1994
DOI: 10.1007/bf02245237
|View full text |Cite
|
Sign up to set email alerts
|

Raised corticosterone in the rat after exposure to the elevated plus-maze

Abstract: Rats given one or two 5-min trials in the elevated plus-maze had plasma corticosterone concentrations significantly higher than the home cage control group and there was no sign of habituation in the group given two trials. In rats given two plus-maze trials the corticosterone responses were significantly higher in the group given 10-min rather than 5-min trials. A previous experience of cat odour (1 week earlier) has no effect on the plasma corticosterone response, but did have an anxiogenic effect that could… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
37
0
3

Year Published

1995
1995
2016
2016

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(50 citation statements)
references
References 16 publications
10
37
0
3
Order By: Relevance
“…control) DBA/2 mice displayed greater avoidance of open arms and, thus, higher levels of anxiety than C57BL/6 mice, which is in accordance with previous observations (Crawley et al, 1997;Griebel et al, 1997;Ohl et al, 2003;Rodgers et al, 1999). On the neuroendocrine level, previous studies reported a significant increase in plasma corticosterone after EPM exposure (File et al, 1994;Holmes et al, 1998). Intriguingly, exposure of our animals to the EPM induced a small, insignificant increase of intrahippocampal corticosterone in both strains, although the EPM represented a ''novel environment''.…”
Section: Article In Presssupporting
confidence: 90%
“…control) DBA/2 mice displayed greater avoidance of open arms and, thus, higher levels of anxiety than C57BL/6 mice, which is in accordance with previous observations (Crawley et al, 1997;Griebel et al, 1997;Ohl et al, 2003;Rodgers et al, 1999). On the neuroendocrine level, previous studies reported a significant increase in plasma corticosterone after EPM exposure (File et al, 1994;Holmes et al, 1998). Intriguingly, exposure of our animals to the EPM induced a small, insignificant increase of intrahippocampal corticosterone in both strains, although the EPM represented a ''novel environment''.…”
Section: Article In Presssupporting
confidence: 90%
“…Hence, selection for high levels of plus-maze anxiety might not necessarily co-select neuroendocrine reactivity, because no correlation was found between behavioral measures of anxiety in the plus-maze test and the increase in ACTH and corticosterone concentrations in both lines. Although exposure to the elevated plus-maze stimulates the HPA axis (File et al 1994;Neumann et al 1998), anxiety-related behavior on the plus-maze has also been demonstrated to be independent of an HPA axis activation (Pich et al 1993). A dissociation between emotionality and HPA reactivity similar to the present results has also been found in the Syracuse (Brush 1991) and Maudsley (Abel 1991) rats, suggesting that endocrine correlates may not be tightly linked to the respective emotionality genotype.…”
Section: Discussionmentioning
confidence: 44%
“…Furthermore, in the study by Henniger et al (13), the high anxiety behavior and low anxiety behavior lines were selected in the elevated plus-maze test. Thus, it is important to note that the elevated plusmaze and the open-field tests are likely to assess different forms of anxiety (22,23). In a recent review, Prut and Belzung (24) concluded that the open-field test may be an animal model of non-pathological anxiety, sensitive to anxiolytic-like effects of classical benzodiazepine and 5-HT1 receptor agonists but not to the effects of compounds displaying anxiolytic-like effects regarding the clinical entity termed "anxiety disorders".…”
Section: Discussionmentioning
confidence: 46%